The use of Geocoding for Home Healthcare Application and Management an Epidemic Situation. Case of COVID-19 Virus Outbreak - Akakba, Ahmed; Lahmar, Belkacem (Geographica Pannonica, 2020)
The lack of an addressing system is one of the problems of urban management in Algeria, which makes it hard to find the addresses concerned, especially in case of crisis where the decision-makers need accurate data in real-time. Like many countries, Algeria follows up the world health organization guidelines that declared the COVID-19 virus as pandemic and recommended the full quarantine and reduces the social contact as much as possible; however, these procedures weren’t enough to control the increasing number of confirmed cases, which exceeded the hospital’s capacities. To face up the outbreak of this pandemic, the Algerian health professionals decided to treat most coronavirus cases at home. This study aims to use a geocoding tool developed in C# programming language and ArcGIS Software Development Kit (SDK) to help in the epidemiological control operation in Ain Touta city and simplifies the interventions using a spatial approach. These problems are addressed by a tool to collect, analyze, store, and process archiving of the geographic data using a geodatabase server